The Employment of Women in the European Union - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2007)
The increasing employment of women in Europe is not only a result of economic restructuring, but also a consequence of changing family structures, changing expectations, changing wage determination mechanisms and increasing urbanisation. Many of the services which have been outsourced from the household sector to the market sector tend to remain almost exclusively a female employment domain. Thus, the areas of production that constitute the domain of female work in traditional societies remain the same in the developed industrial societies; only the degree of marketisation differs. The extent to which domestic work is outsourced depends upon the welfare model. Thus, it is a different set of taxes, transfer payments and public services in the various models which impacts on the relative efficiency and direct and indirect costs of goods and services which can be produced in the household or the market sector. Different institutional settings impact on the opportunity cost of domestic work and/or the shadow price of the domestic good or service, resulting in a divergence of the employment rate of women between the various models in the EU.
Keywords: 330; Employment rates; models of social organisation; marketisation of household production; time use surveys; gender segregation; Weibliche Arbeitskräfte; Arbeitsmarktsegmentation; Hausarbeit; Zeitverwendung; Sozialstaat; EU-Staaten